Transposed basilic vein fistula: A credible option - Leong, Benjamin; Azizi, Zainal Ariffin; Hussin, Hanif; Tajri, Hafizan; Govindarajantran, Naresh; Pillay, Kumaruguru; Tan, Kia Lean; Othman, Ahmad Faidzal (The Editorial Committee of Annals of Vascular Diseases, 2018)
Objective: Native fistula creation for hemodialysis in pa- tients who have exhausted all their superficial veins presents a challenge to vascular practice. We review our experience in transposed basilic vein fistula (BVT) creation and its usage for hemodialysis. Materials and Methods: We analyzed the hospital opera- tive registry from January 2009 till June 2012 to identify the total number of BVT created in our center. Medical records of all patients were traced, and patients were interviewed using a standard proforma. In our center, BVT is performed as a two-stage procedure. All patients were routinely as- sessed with duplex scan preoperatively and postoperatively. Results: Two hundred thirty-nine patients were recruited in the study. Of these patients, 50.6% were male and 49.4% were female. Mean age was 53.4 years. Of these patients, 81.2% had history of other previous fistula creation. Risk factors profile includes diabetes mellitus in 59.8%, hyper- tension in 86.2%, and smoking in 13.0%. Of these patients, 84.5% had no operative complication. Commonest compli- cation was wound infection, 6.3%, followed by hemorrhage or hemotoma required surgical intervention, 5.9%, and pseudoaneurysm, 1.3%. Primary and secondary patencies were at 84.2% and 86.1% at 1 year and 67.7% and 70.5% at 3 years, respectively. Conclusion: BVT is a credible option for challenging pa- tients with absence of superficial veins for native fistula 1 Unit of Vascular Surgery, Department of Surgery, Queen Elizabeth Hospital II, Kota Kinabalu, Malaysia 2 Department of Surgery, Kuala Lumpur Hospital, Kuala Lumpur, Malaysia 3 Department of Surgery, Kulliyah (Faculty) of Medicine, In- ternational Islamic University Malaysia, Kuantan, Malaysia Received: February 1, 2018; Accepted: March 11, 2018 Corresponding author: Benjamin Dak Keung Leong, MS, FRCS. Unit of Vascular Surgery, Department of Surgery, Queen Eliza- beth Hospital II, 88300 Kota Kinabalu, Sabah, Malaysia Tel: +60-12-543-2511, Fax: +60-3-2692-3719 E-mail: bleongdk@yahoo.com creation with good patency and low operative complication rate. Preoperative ultrasound assessment improves patient selection and outcome of BVT.